Analisis VAIC sebagai Determinan Kinerja Keuangan pada Perusahaan Perbankan di Bursa Efek Indonesia - Salmariana Pasaribu; Jojor Lisbet Sibarani; Eli Safrida; Khanti Listya (Politeknik Ganesha Medan, 2025)
The advancement of technology in the digital era and the increasing competition in the banking industry demand that companies not only rely on physical assets but also leverage intellectual capital to enhance financial performance. Intellectual capital comprises physical capital, human capital, and structural capital, which must be effectively managed to create value ad ded and maintain competitiveness. This study aims to examine the effect of intellectual capital on financial performance, measured by Return on Assets. It addresses the research gap arising from inconsistent findings in previous studies regarding the impact of intellectual capital components on profitability, as well as the limited focus on the Indonesian banking sector in the post-pandemic period (2020–2024), a critical era of accelerated digital transformation. This study employs the VAICTM (Value Added Intellectual Coefficient) method to measure intellectual capital, with its components Value Added Capital Employed, Value Added Human Capital, and Structural Capital Value Added as independent variables. Using purposive sampling, 19 out of 47 banking companies listed on the Indonesia Stock Exchange were selected. Data were analyzed through multiple linear regression using SPSS. The findings reveal that VACA, VAHU, and STVA each have a positive and significant effect on financial performance. The research model yields an Adjusted R² of 0.684, indicating that 68.4% of the variation in ROA is explained by intellectual capital. These results provide empirical evidence of the importance of intellectual capital in enhancing bank profitability and offer practical implications for banking management in optimizing intellectual resources.